Precision Diagnostics in Transplantation: From Bench to Bedside. Issue 3 (27th December 2012) - Mengel, M.; Campbell, P.; Gebel, H.; Randhawa, P.; Rodriguez, E. R.; Colvin, R.; Conway, J.; Hachem, R.; Halloran, P. F.; Keshavjee, S.; Nickerson, P.; Murphey, C.; et al.
<x xml:space="preserve">Abstract</x> The Canadian and American Societies of Transplantation held a symposium on February 22, 2012 in Quebec City focused on discovery, validation and translation of new diagnostic tools into clinical transplantation. The symposium focused on antibody testing, transplantation pathology, molecular diagnostics and laboratory support for the incompatible patient. There is an unmet need for more precise diagnostic approaches in transplantation. Significant potential for increasing the diagnostic precision in transplantation was recognized through the integration of conventional histopathology, molecular technologies and sensitive antibody testing into one enhanced diagnostic system.